Determinants of Mortality among Low Birthweight Infants During Hospitalization in Karangasem District Hospital - I Ketut Duara; Dewa Nyoman Wirawan; Pande Putu Januraga; Anak Agung Sagung Sawitri (Universitas Udayana, 2016)
Background and purpose: Infant mortality rate in Indonesia is still high and is largely related to low birthweight (LBW) infants. Previous studies reported the sociodemographic and clinical factors as determinants of mortality of LBW infants, but rarely examined factors related to their health services. This study aims to determine the demographic, clinical and health services as determinants of mortality of LBW infants during hospitalization. Methods: This study was a retrospective using cohort data of medical record of LBW infants in Karangasem Hospital since January 2012 to October 2014. Logistic regression was done to determine the relationship between demographic, clinical and health services factors with LBW infants’ mortality. Results: The proportion of mortality among LBW infants during hospitalization was 12.12%. Most parents (64.6%) live in good access to health services. The proportion of female infants (51.4%) was higher than male. LBW infants who were born in hospital (85.7%) greater than born outside hospital. Vaginal delivery (75.3%) was greater than C-section. Preterm infants (57.1%) was greater than at term with median of birthweight was 2100 grams. Proportion of asphyxia, respiratory distress syndrome (RDS), sepsis, hypoglycemia and hypothermia, respectively 24.1%, 4.66%, 0.78%, 7.92% and 3.73%. Variables associated with LBW mortality were increasing of 50 grams of birthweight, asphyxia, RDS and referred infants. Conclusion: The mortality of LBW infants during hospitalization was 12.12% with increasing of 50 grams of birthweight,